About the mechanism of formation of polycrystalline n-ZnO/p-CuO heterojunction - Adilov, Sh.R.; Kumekov, M.E.; Kumekov, S.E.; Terukov, E.I. (Recent Contributions to Physics, 2012)
The model of formation of heterojunction on the basis of polycrystalline films of zinc and copper oxides is considered. On the basis of the analysis of crystal structure of zinc and copper oxides it is carried sides of elementary cells between which out epitaxy parities are revealed. It is shown also, that alongside with performance of a rule epitaxy parities the affinity of values of ionic radiuses double charged ions Cu ++ and Zn ++ enables the realization of polycrystalline heterojunction in system ZnO/CuО.